South Asian transnational marriages in comparative perspective - CHARSLEY, KATHARINE; SHAW, ALISON (Global Networks, 2006)
Abstract This issue on South Asian transnational marriages brings diverse practices and networks into detailed ethnographic focus. Gender and agency are key themes explored in the collection, as well as the potential and actual transformation of gendered status resulting from marrying a migrant or joining a spouse overseas. The introduction identifies some common threads. Several articles challenge the assumption of wives' passivity in arranged marriages or in their joining husbands overseas, while one highlights the less-documented experiences of men who migrate to join wives working abroad. The collection also offers insights into the cultural and emotional reasons for such marriages, complementing analyses that stress strategic motivations, and noting the emotional consequences of separation and new household formations for the experiences of marriage and parenthood. Marriage emerges as an important means of producing and transforming transnational networks, while marriage practices and dynamics are themselves transformed in the process.
Keywords: 2000 à aujourd'hui; 2000-2009; anthropologie; approches et analyses; asie; asie du sud; cours; discipline; ethnographie; histoire et politique; mariage; migration; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques

Aspiration, reunification and gender transformation in Jat Sikh marriages from India to Canada - MOONEY, NICOLA (Global Networks, 2006)
In this article I explore marriage as a strategy of family migration among a transnational community of middle-class Jat Sikhs. Family reunification and status aspirations are examined as central concerns of the transnational movement of Jat Sikhs from India to Canada. It is argued that Jat Sikh transnationalism and gender are mutually-constitutive: migration strategies can construct women, as well as men, as agents of marital citizenship, and in facilitating migration, transnational marriage may transform practices and notions of gender and status. The article is based on preliminary ethnographic research among Jat Sikh brides in Toronto and Vancouver, and forms part of a larger study of gender, modernity and identity in Indo-Canadian Jat Sikh marriages.
Keywords: amériques; anthropologie; approches et analyses; asie; canada; colombie-britannique; cours; discipline; famille; histoire et politique; inde; intersectionnalité; justice sociale; mariage; mariages transnationaux; migration; ontario; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; toronto; vancouver

‘Who is the Developed Woman?’: Women as a Category of Development Discourse, Kumaon, India - Klenk, Rebecca M. (Development and Change, 2004)
This article analyses gendered discourses of development in rural North India, and addresses the usefulness of recent scholarship on development as ‘discourse’ for understanding connections between development and subjectivity. This scholarship is an excellent point of departure for exploring the contradictions inherent in the institutionalization of economic development and the global reach of its discourses, but it has focused primarily upon development as discourse at official sites of deployment, while paying less attention to how specific discourses and processes of development are appropriated by those constituted as beneficiaries of development. The under-theorization of this aspect has meant that the range of processes through which development projects may encourage new subject positions are poorly understood. By investigating what some women in rural Kumaon have made of their own development, this article contributes to emerging scholarship on development and subjectivity with an ethnographic analysis of the polysemic enthusiasm for development expressed by some of its ‘beneficiaries’.
Keywords: Kumaon; anthropologie; approches et analyses; asie; cours; discipline; développement; féminisme décolonial; histoire et politique; inde; pol4022; premier cycle; relations internationales; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; thématiques